A Note on a Group Preference Axiomatization with Cardinal Utility - Dias, Luís (2012)
Kenneth Arrow’s work on social welfare proposed a set of conditions that a function to aggregate ordinal preferences of the members of a group should satisfy, proving that it was not possible to satisfy all these assumptions simultaneously. Later, Ralph Keeney adapted these conditions and proposed a cardinal utility axiomatization for the problem of aggregating the utility functions. This note discusses in particular the condition of nondictatorship. It proposes stronger formulations for this condition to limit the maximum influence that an individual can have, and it presents the corresponding characterization of compliant group cardinal utility functions. An extension to address coalitions of individuals acting strategically is also discussed.